Read Aloud pada Pembelajaran Berdiferensiasi untuk Meningkatkan Literasi Siswa Lambat Belajar - Yenicke Bara Nurdyana (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The research was conducted to test of the read-aloud method in increasing the literacy of slow-learning students in elementary schools through differentiated learning. This type of research uses experimental methods. The research method used is pre-experimental design. The research was designed using a one-group pre-test post-test design. In the research, a diagnostic test was carried out at the beginning of learning, and then treatment was carried out using the read-aloud method during learning. At the end of the research, a final test was given to determine the learning outcomes. Data collection techniques use observation, tests, and documentation. The research subjects were slow-learning students in class II of Tunjung 1 State Elementary School, Bangkalan Regency. Using a two-sample F-test for variances, three students with special needs were identified as still very low in reading comprehension, with an average diagnostic score of 11.11%. The initial hypothesis is that there will be an increase in the literacy of slow-learning students through the read-aloud method. The research results show that the significance level value of the data is smaller than the significance level value (0.050), namely 0.003. It is known that the significance level value (α) = 0.003 < 0.050, meaning that the hypothesis of this research can be proven and accepted. The read aloud method is believed to be able to improve the literacy skills of slow learning students and can be used as a differentiated learning method in the elementary schools studied.